Correlation of influent characteristics and operation parameters with disinfection efficiency in view of chlorine dosage reduction in domestic wastewater - Gutierrez, Ruby Rose C. (College of Engineering, University of the Philippines Diliman, 2015)
Municipal wastewater contains different pathogenic microorganism, and its safe discharge to receiving body of water is a major concern of wastewater treatment plants. For several years now, chlorine disinfection has been deemed the well-established and effective technology against a wide spectrum of pathogenic microorganism for being economical, efficient and readily available.This research highlights different interferences with chlorine demand in a wastewater treatment plant were the chlorine residual in the effluent can prolong disinfection.Six wastewater treatment facilities were evaluated in terms of the parameters that significantly(p<0.05) correlates with chlorination disinfection efficiency, The parameters Include BOD, COD,TSS, NH4+, NO3-, iron, manganese pH and temperature, The organic and inorganic substances highly to the chlorine demand in a disinfection process thus, there should be efficient organic removal in the system to be able to reduce chlorine demand as well. Laboratory simulation for the kinetics of pathogen die off was found to be in the first-order.Coliform die-off rate becomes slower as the COD concentration to be treated increase. On the other hand, as the chlorine does increases the coliform die off rate becomes faster due to more available chlorine for disinfection.